LOOKING AT NETIZEN RESPONSES ABOUT FREE NUTRITIOUS MEALS (MBG) ON @PRABOWO'S INSTAGRAM POST ON FEBRUARY 10, 2025 - Jasmin, Afifa Syahira; Sazali, Hasan (International Journal of Cultural and Social Science, 2025)
This study is done in order to figure out how netizens form, negotiate and communicate meaning on A nutritious program (MBG) through a comment on instagram account @prabowo. With a qualitative approach and a virtual ethnographic method. The study Employing the symbolic interactionism theory of Herbert blumer with 3 main foundation namely, meaning, language, thought. The results of this study are in the form of meaning, netizens interpret MBG not only based on information but from the meaning they feel in real life. Language, social interaction forms a collective meaning regarding the gap in state budget priorities, with symbols as markers of social and emotional meaning; "PHK", "3T", "gas queue". Thoughts, netizen comments reflect awareness of their life experiences and social positions, this shows that the process of forming meaning involves self-reflection.